Prominent 946 lines induced from flashlamp pumped Nd: YAG rod - Bidin, Noriah (American Institute of Physics, 2012)
Spectroscopic properties of Nd:YAG laser rod pumped by a new developed flashlamp is investigated. A new power supply is constructed to power xenon flashlamp. A 1 at.% Nd:YAG laser rod is transversely pumped by the flashlamp and stabilized by a water cooling system operated at ambient temperature of 20°C. The absorption and emission spectrum of the flashlamp pumped Nd:YAG rod is analyzed via spectroscopy technique. The peak absorption line is identified to be at 882 nm. The dominant emission line obtained from transition 4F3/2→4I9/2 comprised of quasi three level laser at 938.5 and 946 nm with the corresponding cross section of 2.42×10-19cm2 and 3.04×10-19cm 2 respectively. This cross section is found almost ten times greater than the usual one.